How can local Governments become Pioneers in Tourism Development? Analysis of Organizational Performance and Influencing Factors - Mulyawan, Wawan (Department of Government Studies, Universitas Muhammadiyah Buton., 2024)
This study examines the pivotal role of accountability and responsibility, together with the influence of organizational structure, human resource capabilities, and financial management, in enhancing the performance of tourist sector growth in Bima Regency. This study employs qualitative primary and secondary data-gathering techniques, including interviews, documentation analysis, and direct observation. The research informants included officials from the Bima Regency Culture and Tourism Service, Village Heads, and community leaders in the local government. The research findings indicate that the regional government's dedication to performance accountability, achieved through the transparent allocation of budget and monitoring of tourism destination performance, along with its responsibility to preserve the environment, develop sustainable products, and promote community participation, establishes a harmonious equilibrium between economic growth and environmental sustainability. A well-designed organizational structure promotes efficient coordination and decision-making, while improved human resource skills and prudent financial management bolster the success of tourist development programs, establishing a strong basis for sustained growth in Bima Regency. This study offers valuable insights into how local governments may lead tourist development by prioritizing accountability, responsibility, organizational structure, and efficient administration of human and financial resources.